Pengembangan Kompetensi Guru dalam Mengimplementasikan Pengembangan Projek Profil Pelajar Pancasila - Hindriana, Anna Fitri; Abidin, Zaenal; Arif, Asep Ginanjar; Setiawati, Ina; Aziz, Abdul (Empowerment, 2023)
The implementation of Kurikulum Merdeka is a policy to restore the learning process after the Covid-19 pandemic. The aim of the Kurikulum Merdeka is not only to develop student intelligence but also to develop student character in accordance with the values in Pancasila. The characters is developed through the project of Pancasila  Student Profile (In Indonesian: Pengembangan Projek Profil Pelajar Pancasila - P5). The P5 requires a deep understanding of the notion of P5, the theme in P5 implementation, and the method to develop P5 modules. Building on the necessity for the project implementation, this community service aims to provide knowledge about the implementation of P5 and assistance in developing P5 modules. The activity in the community service includes 1) teacher training on the principles of Pancasila student profile development in the implementation of P5, and 2) further assistance in developing P5 module, especially in the relation between the themes, the flow of activities, reflection process and evaluation process. The results of the activities were observed in the increase in teachers' understanding of the implementation of P5 and the improvement in the quality of the P5 module designImplementasi kurikulum merdeka merupakan suatu kebijakan untuk melakukan pemulihan pembelajaran setelah masa pandemi covid-19. Implementasi kurikulum merdeka tidak hanya bertujuan mengembangkan kecerdasan siswa saja namun juga mengembangkan karakter sesuai dengan nilai-nilai Pancasila, pengembangan karakter yang sesuai dengan nilai – nilai Pancasila dapat dilakukan melalui kegiatan Pengembangan Projek Profil Pelajar Pancasila (P5). Implementasi P5 memerlukan pemahaman yang mendalam terhadap pemahaman P5, penentuan tema dalam pelaksanaan P5, dan pengembangan modul P5. Tujuan pengabdian masyarakat ini adalah untuk memberikan pengetahuan tentang implementasi P5 dan pendampingan pengembangan modul P5. Metode dalam kegiatan ini adalah 1) pelatihan kepada guru-guru tentang prinsip-prinsip pengembangan profil pelajar pancasila pada implementasi P5, dan 2) pendampingan pengembangan modul P5 terutama keterkaitan antara tema, alur kegiatan, refleksi dan evaluasi. Hasil yang dicapai adalah peningkatan pemaham guru-guru terhadap implementasi P5 serta peningkatan kualitas rancangan modul P5.